Social Legal Consciousness or Legal Culture? - H. Szilágyi, István (Public Governance, Administration and Finances Law Review, 2023)
In contemporary legal sociology research, legal culture and legal consciousness are often used as synonymous or closely related, overlapping concepts. The aim of this paper is to elucidate the possibility of separating the two concepts through a more in-depth analysis. The first part of the paper explores the ideological-historical connections between the two concepts and argues that the conceptual confusion between legal culture and legal consciousness that characterises contemporary legal sociology occurred in the 1970s in American legal scholarship. The concept of social legal consciousness is first discussed in the context of conceptual analysis. After a general definition of legal consciousness, the components of individual legal consciousness, the factors and mediating structures linking individual and social legal consciousness, and finally the theoretical issues of conceptualisation are discussed. The second part of the conceptual analysis focuses on the concept of legal culture. The difficulties of defining the concept are taken into account, starting from a review of the academic debate surrounding the work of Lawrence Friedman. The concept of legal culture is constructed on the basis of the criteria for conceptualisation derived from this. The core concept is culture, and the distinguishing feature is a sociological concept of law. Next, it introduces the distinction between lay and professional culture and examines the extent to which the concept of legal culture thus outlined meets the criteria set out above. The paper concludes by summarising the rationale and yields of the conceptual analysis, highlighting the dynamic relationship between legal culture and social legal consciousness.